KEPEMIMPINAN EFEKTIF KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU DAN TENAGA KEPENDIDIKAN DI ERA TRANSFORMASI - Hasnadi Hasnadi (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2026)
Schools as educational institutions need to be managed properly through the leadership of the principal. Effective leadership is a leadership model that focuses on the development of instructional, organizational, school personnel, educational services, relationships and communication. This article aims to analyze and describe effective leadership at SMPIT Teuku Umar, West Aceh Regency. This research is a qualitative research. The research subjects were principals, vice principals, teachers and education staff. Data were collected through interviews, observations, and document studies. Data analysis is done by: data reduction, display data and conclude. The results of the study indicate that the principal has tried to apply effective leadership which can be seen from the competencies possessed, the ability to influence and communicate, apply a leadership style that is appropriate to the situation and conditions, involve all relevant elements ranging from decision making, implementation of activities and evaluations, work in strong teamwork, maintaining and maintaining a conducive school climate, developing human resource competencies. The research found that effective leadership can create a positive work culture in madrasas and impact the competency of teachers and education staff. The leadership of the madrasah principal plays a significant role in building a collaborative culture, allowing teachers and education staff to share experiences and knowledge.